2021
DOI: 10.1002/ajp.23265
|View full text |Cite
|
Sign up to set email alerts
|

Stress behaviors in captive robust capuchins: Effects of humidity, visitors, management and sex

Abstract: Wild robust capuchins (Sapajus spp.) are omnivorous neotropical primates that live in relatively large groups in extensive home and daily ranges with activity budgets dominated by traveling, foraging, and object manipulation, meaning that enclosed spaces can result in significant deprivation. Space restriction, manipulation by caretakers, and the chronic presence of visitors, can disrupt the animals' welfare, altering their normal activities and inducing stress behaviors. We aimed to study the behavioral reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Interestingly, we found a positive and significant relationship between the daily number of people observed in the fragment and UW—but not between the daily number of human‐monkey interaction and UW, nor between the interaction of these two predictive variables and UW—which indicates people as a direct or at least as an indirect stimulus for our capuchins to display more UW. At first sight, our findings could indicate that the animals use UW behavior to relieve stress caused directly by the presence of people, who are known to be a source of stress for capuchins, even when these animals are used to the presence of visitors (de la Barrera Cardozo et al, 2021; Sherwen et al, 2015). People can also cause stress indirectly, because the food they provide can increase the disputes between the monkeys (Hsu et al, 2009; Ram et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly, we found a positive and significant relationship between the daily number of people observed in the fragment and UW—but not between the daily number of human‐monkey interaction and UW, nor between the interaction of these two predictive variables and UW—which indicates people as a direct or at least as an indirect stimulus for our capuchins to display more UW. At first sight, our findings could indicate that the animals use UW behavior to relieve stress caused directly by the presence of people, who are known to be a source of stress for capuchins, even when these animals are used to the presence of visitors (de la Barrera Cardozo et al, 2021; Sherwen et al, 2015). People can also cause stress indirectly, because the food they provide can increase the disputes between the monkeys (Hsu et al, 2009; Ram et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Social hypotheses propose that monkeys perform UW to communicate about sexual condition (Boinski, 1992; Campos & Fedigan, 2013; Jones, 2003; Miller et al, 2008; Milton, 1985; Phillips et al, 2011; Strier, 2021), to demarcate an area (Campos & Fedigan, 2013; Charles‐Dominique, 1977; Milton, 1975), to communicate an identity or hierarchical status that facilitate the assessment of quality, promoting the possibility of decreasing the likelihood of aggression, appeasing social conflicts (Fragaszy et al, 2004; Heymann, 1995; Jones, 2003; Milton, 1975; Oppenheimer & Oppenheimer, 1973; Ueno, 1994), or to relieve tensions after agonisms, when the victim's anxiety levels typically increase and it could displays UW as a displacement behavior (Jones, 2003; Miller et al, 2008; Milton, 1975, 1985; Strier, 2021). Interestingly, if UW serves to relieve tensions, UW itself could be viewed as a behavioral indicator of disruption in the animals’ welfare ( sensu Berger‐Tal et al, 2011), since frequent displacement behaviors is an indication of animal stress (e.g., de la Barrera Cardoso et al, 2021). However, various studies have refuted the role of UW in sexual function (Carnegie et al, 2005; Carosi et al, 2005; Roeder & Anderson, 1991; Schino et al, 2011), demarcation (Campos & Fedigan, 2013; Carosi et al, 2005; Heymann, 1995; Roeder & Anderson, 1991), hierarchy (Schino et al, 2011), and appeasement (Roeder & Anderson, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal animal sampling was used for descriptive analysis of 70 hours of behavior observation [11]. Wagner et al observed the behavior of capuchin monkeys in the public Zoo of Vers-Duifen, Brazil, for 40 days to determine the frequency of stereotypical behavior and self-orientation and to analyze the effects on behavioral stability [12]. In addition to zoos, the stereotypical behavior of monkeys in research facilities was observed and analyzed [13].…”
Section: Introductionmentioning
confidence: 99%